The Influence of Job Characteristics on Job Satisfaction, Organizational Commitment, and Managerial Performance: A Study on Construction Companies in Central Java - Djastuti, Indi (Universitas Prasetiya Mulya, 2010)
The objective of this research is to analyze and to test the influence of Job Characteristics, Job Satisfaction, and Organizational Commitment on Managerial Performance. There are six hypotheses proposed in this study i.e. 1) the influence of job characteristics on job satisfaction of managerial employee. 2) The influence of job satisfaction on organizational commitment of managerial employee. 3) The influence of job characteristics on organizational commitment of managerial employee 4) the influence of job characteristics on performance of managerial employee 5) the influence of job satisfaction on performance of managerial employee 6) the influence of organizational commitment on performance of managerial employee. Based on the final data analysis, all proposed hypotheses are accepted. Autonomy and task identity have greatest contribution to the job characteristics variable. The continuant commitment has a great contribution to organizational commitment variable. However, satisfaction to the supervisor contributes substantially to job satisfaction variable. While, team work, initiative and reporting activities have greatest contribution to the performance of managerial employee variable. The research shows that organizational commitment variable as intervening variable that bridging the relationship between job characteristics variable and managerial employee performance variable. Path coefficient for organizational commitment variable is greater than job satisfaction variable in influencing managerial employee performance. Therefore, in order to enhance performance of managerial employees, it is necessary to build stronger organizational commitment, especially affective commitment.